Identificação de áreas potencializadoras de inundações e enxurradas: uma proposta metodológica aplicada na Bacia Arroio dos Pereiras, Irati PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Flood processes have become increasingly worrying when it comes to measures to be taken in urban planning. In this sense, the objective of this thesis is to understand the floods and floods when identifying potential areas of these processes in the Arroio dos Pereiras Basin in the Municipality of Irati-PR. The methodology of the Index of Potentializing Areas of Flood and Enxurradas (IAPIE) was proposed, through which it is possible to identify which areas of an urban river basin present greater potential to trigger floods in downstream areas. In addition, the methodology can be used in the elaboration of future scenarios of use and occupation of the basin under analysis, through the parameters: Precipitation, Infiltration of water in the soil, Declivity, Water Balance, Morphometry and Soil Types. Initially the sectorization of the studied basin should be carried out and each parameter will be analyzed, by sector, through quantitative and qualitative classifications of the same. The Precipitation parameter considers precipitation values by means of pluviograms that use monthly rainfall totals in a given place and in the chosen period; the Infiltration Capacity of water in different uses is identified through detailed maps of land use; the parameter Declivity identifies the areas with greater or lesser potential of water flow; the Water Balance accounts for the water availability of a region on a climatological and comparative basis; the Morphometric Susceptibility, evaluates morphometrically the basins that present greater conditions in the development of floods and floods, through parameters that have direct connection with the occurrence of these phenomena and the last parameter Types of Soils, evaluates the permeability capacity of Soils. Through the application of the IAPIE, it was possible to identify that sector 2, corresponding to the Center of the city of Irati, increases the occurrence of floods and floods in the Arroio dos Pereiras Basin by 57.11%. This is due to the high rate of waterproofing of the soil, since in this sector are concentrated commercial and service activities, as well as residences. The sector that has the least influence on the occurrence of floods and floods is the 6, located in the high course of the basin (Rural Area), contributing with 33.31%. For this sector, policies that encourage the permeabilization of the soil must be considered, since it is an area where the deepest soils are found, which provides water infiltration. Due to the current condition determined by IAPIE, sector 6 has low potential in the influence of floods and floods, however, if the waterproofing of the area is increased, this sector can be characterized with average potential in the occurrence of floods and floods. In this perspective, if there are changes in land use and occupation in the Arroio dos Pereiras Basin, which waterproof the soil, the occurrence of floods and floods can be potentiated in areas where they already occur and may occur in areas that have not yet been affected by these phenomena.
Keywords: Bacia Hidrográfica; Impermeabilização do solo; IAPIE; Escoamento superficial; Hydrographic Basin; Soil waterproofing; IAPIE; Surface drainage; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA